KATA-KATA TABU DALAM BAHASA INGGRIS DAN BAHASA BURU (SUATU ANALISIS KONTRASTIF) - DAWAN, SRIYATI; RATTU, JULTJE A.J.; PAMANTUNG, RINA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â  This study is entitled â€œTaboo Words in English and Buru Language: A Contrastive Analysisâ€. The objective of this research are to identify and classify taboo words in English and Buru language and to analyze the differences between the two languages. This research use descriptive method, which take three steps to complete this research. In the preparation writer reads some books and journals about taboo words, the data in English itâ€™s collected through English books. Data on taboo words in Buru language were collected by interviws with several informants, especially in Basalale Village, Waelata sub-district. The informants are native speakers of the Buru language, aged 30-60 years, who have no disruption in pronunciation and still have good language skills. The data of English and Buru language are classified, analyzed and explained using a theory from Wardhaugh (1986), and data from both languages are contrasted using the theory of Lado (1975). Classification based Wardhaugh's theory, six types of taboo words were found including sex, body function, animals, excretion, death and religion.Â  Taboo words in Buru language found eight types of taboo words, sex, body function, animals, excretion, death, religion, curse and address terms.Â Â Â Â Â  Keywords: Taboo Words: English, Buru Language; Contrastive analysis, sociolinguistics